THE REFLECTION AS THE MAIN COMPONENT OF LEARNING ACTIVITIES OF STUDENTS - Бондар, Л. В.; Ісхакова, Н. Г. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article is devoted the level of reflexes оf students. The features of self- reflection were explained. The article analyzes the reflexive actions wich must be in training activities. The reflection plays an important role in the development of personality. Based on the empirical research has been formulated conclusion: the reflection forms of learning have to use in the learning process of first-year students